2015
DOI: 10.18632/oncotarget.3629
|View full text |Cite
|
Sign up to set email alerts
|

Targeting AMPK for cancer prevention and treatment

Abstract: AMP-activated protein kinase (AMPK) is an important mediator in maintaining cellular energy homeostasis. AMPK is activated in response to a shortage of energy. Once activated, AMPK can promote ATP production and regulate metabolic energy. AMPK is a known target for treating metabolic syndrome and type-2 diabetes; however, recently AMPK is emerging as a possible metabolic tumor suppressor and target for cancer prevention and treatment. Recent epidemiological studies indicate that treatment with metformin, an AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
238
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(253 citation statements)
references
References 148 publications
11
238
1
3
Order By: Relevance
“…At the same time, activated AMPK stimulates catabolism of fatty acids and glucose uptake. Additionally, AMPK inhibits cell proliferation by stabilizing the tumor suppressors tuberous sclerosis 2 protein and p53 and by regulating the cyclin-dependent kinase inhibitors p21 and p27; this implicates AMPK as a potential target for cancer treatment (51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, activated AMPK stimulates catabolism of fatty acids and glucose uptake. Additionally, AMPK inhibits cell proliferation by stabilizing the tumor suppressors tuberous sclerosis 2 protein and p53 and by regulating the cyclin-dependent kinase inhibitors p21 and p27; this implicates AMPK as a potential target for cancer treatment (51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that activation of AMPK by pharmaceuticals or natural compounds, e.g. bitter melon extract (BME), is able to block the malignant cell growth in numerous human cancers [42][43][44][45][46]. Indeed, previous studies reported by our team showed that pharmaceutical AMPK activators such as 5-aminoimidazole-4-carboxamide 1-β-D-ribofuranoside (AICAR) (ATP-dependent) and A23187 (ATP-independent) could be used to suppress cervical cancer cell growth harboring with or without LKB1, an upstream kinase of AMPK [44].…”
Section: Amp-activated Protein Kinase In Human Cancer and Its Signifimentioning
confidence: 99%
“…Recently, activation of the AMPK signaling pathway has been shown to play a critical role in regulation of energy metabolism under both physiological and pathological conditions via downstream pathways relevant to the control of cellular proliferation (16,17). AMPK is known to function as an intracellular energy sensor, being activated in response to an increased AMP⁄ATP ratio, a condition of energetic stress, to promote the catabolic pathway, thereby inhibiting cell proliferation (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence now indicates that cancer metabolism mediates cancer development and progression via its activation of related signaling pathways, such as the AMP-activated protein kinase (AMPK) pathway (16,17). Under metabolic stress conditions, where decreases in intracellular ATP and increases in AMP levels are common, AMPK is activated by phosphorylation of a critical amino acid residue (Thr172) to function as a major metabolic switch that maintains energy homeostasis (18,19).…”
Section: Introductionmentioning
confidence: 99%